Ferrous sulfate supplementation causes significant gastrointestinal side-effects in adults: a systematic review and meta-analysis. - Zoe Tolkien; Lynne Stecher; Adrian P Mander; Dora I A Pereira; Jonathan J Powell (PLoS ONE)
Background The tolerability of oral iron supplementation for the treatment of iron deficiency anemia is disputed. Objective Our aim was to quantify the odds of GI side-effects in adults related to current gold standard oral iron therapy, namely ferrous sulfate. Methods Systematic review and meta-analysis of randomized controlled trials (RCTs) evaluating GI side-effects that included ferrous sulfate and a comparator that was either placebo or intravenous (i.v.) iron. Random effects meta-analysis modelling was undertaken and study heterogeneity was summarised using I2 statistics. Results Forty three trials comprising 6831 adult participants were included. Twenty trials (n = 3168) had a placebo arm and twenty three trials (n = 3663) had an active comparator arm of i.v. iron. Ferrous sulfate supplementation significantly increased risk of GI side-effects versus placebo with an odds ratio (OR) of 2.32 [95% CI 1.74-3.08, p<0.0001, I2 = 53.6%] and versus i.v. iron with an OR of 3.05 [95% CI 2.07-4.48, p<0.0001, I2 = 41.6%]. Subgroup analysis in IBD patients showed a similar effect versus i.v. iron (OR = 3.14, 95% CI 1.34-7.36, p = 0.008, I2 = 0%). Likewise, subgroup analysis of pooled data from 7 RCTs in pregnant women (n = 1028) showed a statistically significant increased risk of GI side-effects for ferrous sulfate although there was marked heterogeneity in the data (OR = 3.33, 95% CI 1.19-9.28, p = 0.02, I2 = 66.1%). Meta-regression did not provide significant evidence of an association between the study OR and the iron dose. Conclusions Our meta-analysis confirms that ferrous sulfate is associated with a significant increase in gastrointestinal-specific side-effects but does not find a relationship with dose.